Vasoplegic syndrome in patients undergoing heart transplantation - Qin, Tong-xin; Yao, Yun-tai, the Evidence in Cardiovascular Anesthesia(EICA) Group (Frontiers in Surgery, 2023)
Vasoplegic syndrome is a common life-threatening complication that increases early mortality in patients undergoing heart transplantation. The objective was to summarize the risk factors, onset time and treatment of vasoplegic syndrome in patients undergoing heart transplantation. PubMed, OVID, CNKI, VIP and WANFANG databases were searched with the terms “vasoplegic syndrome,” “vasoplegia,” “vasodilatory shock,” and “heart transplant*,” to identify relevant articles. Data regarding patient characteristics, vasoplegic syndrome manifestation, perioperative management, and clinical outcomes were extracted and analyzed. Nine articles, with 12 patients aging from 7-to 69 years-old, were included. Onset time of vasoplegic syndrome varied from intraoperatively to two weeks postoperatively, including nine (75%) intraoperatively, and all patients were insensitive to vasoactive agents. Methylene blue, angiotensin Ⅱ, ascorbic acid and hydroxocobalamin have been used to treat refractory vasoplegic syndrome.